New active diode with bulk regulation transistors and its application to integrated voltage rectifier circuit - Ryoichi Miyauchi; Koichi Tanno; Hiroki Tamura (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper describes new active diode with bulk regulation transistors and its application to the integrated voltage rectifier circuit for a biological signal measurement system with smartphone. The conventional active diode with BRT has the dead region which causes leak current, and the output voltages of the application (e.g. voltage rectifier circuit) decrease. In order to overcome these problem, we propose new active diode with BRT which uses the control signal from the comparator of active diode to eliminate the dead region. Next we apply the proposed active diode with BRT to the integrated voltage rectifier circuit. The proposed active diode with BRT and voltage rectifier circuit were fabricated using 0.6 μm standard CMOS process. From experimental results, the proposed active diode with BRT eliminates the dead region perfectly, and the proposed voltage rectifier circuit generates + 2.86 V (positive side) and - 2.70 V (negative side) under the condition that the amplitude and frequency of the input sinusoidal signal are 1.5 V and 10 kHz, respectively, and the load resistance is 10 kΩ.